2020
DOI: 10.1001/jamainternmed.2019.4446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Tailored, Family-Involved Hospital Elder Life Program on Postoperative Delirium and Function in Older Adults

Abstract: IMPORTANCE Postoperative delirium (POD) is a common condition for older adults, contributing to their functional decline.OBJECTIVE To investigate the effectiveness of the Tailored, Family-Involved Hospital Elder Life Program (t-HELP) for preventing POD and functional decline in older patients after a noncardiac surgical procedure. DESIGN, SETTING, AND PARTICIPANTSA 2-arm, parallel-group, single-blind, cluster randomized clinical trial was conducted from August 24, 2015, to February 28, 2016, on 6 surgical floo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 33 publications
0
100
0
3
Order By: Relevance
“…Second, early approaches for delirium prevention and management must be adapted. The Hospital Elder Life Program provides creative approaches that comprise several intervention methods, such as providing tablet computers for remote coaching and communication by professionals, volunteers, or family members and providing sleep enhancement methods [12,13]. Early interventions for adequate programmes for COVID-19 patients, especially elderly patients, are necessary.…”
mentioning
confidence: 99%
“…Second, early approaches for delirium prevention and management must be adapted. The Hospital Elder Life Program provides creative approaches that comprise several intervention methods, such as providing tablet computers for remote coaching and communication by professionals, volunteers, or family members and providing sleep enhancement methods [12,13]. Early interventions for adequate programmes for COVID-19 patients, especially elderly patients, are necessary.…”
mentioning
confidence: 99%
“…The data from our study relate visual deficit to delirium and drug administration. Other investigations do this as well, such as the one carried out by Inouye et al [ 21 ]. In their study, they showed that acting on variables that are expected to increase the risk of developing delirium could reduce the number and duration of episodes of this syndrome in hospitalized patients.…”
Section: Discussionmentioning
confidence: 67%
“…When these interventions are delivered by family members, the number needed to treat to prevent 1 case of postoperative delirium was 5.9 (95% CI: 4.2-11.1). 34 Fluid fasting for more than 6 h is an independent risk factor for postoperative delirium (OR = 10.6; 95% CI: 1.4-78.6). 35 Thus, when the surgery is elective, patients at higher risk for delirium should be prioritized for surgery earlier in the day to reduce unanticipated prolonged preoperative fasting, sleep alteration, and interruption of medication schedules.…”
Section: Nonpharmacologic Delirium Preventionmentioning
confidence: 98%